Comparative analysis of the fecal microbiota in Père David's deer and five other captive deer species - Zhao, Caiquan; Yang, YuChen; Zhao, Peng; Bai, LiGe (Frontiers in Microbiology, 2025)
IntroductionGut microbes are essential for host nutrition, immunity, and development. Various factors influence the composition and function of the gut microbial community. However, there is limited knowledge regarding the comparison of gut microbiota across different deer species, particularly those in the World Deer Park of Baotou (Inner Mongolia, China).MethodsThis study utilized 16S rRNA gene amplicon sequencing to analyze the fecal microbiota and potential microbial function in Père David's Deer (Elaphurus davidianus), Sika deer (Cervus nippon), American Wapiti (Cervus canadensis), Red Deer (Cervuselaphus), Fallow Deer (Dama dama), and Reindeer (Rangifer tarandus).Results and discussionThe findings indicated no significant differences in alpha diversity, yet there was a noteworthy distinction in beta diversity among the six deer groups. At the phylum level, the predominant bacteria in the deer populations were Firmicutes, Bacteroidetes, and Proteobacteria. At the genus level, 54 core bacterial microbiota were identified. The top four genera in AW, FD, PD, and SD were Ruminococcaceae UCG-005, Rikenellaceae RC9 gut group, RuminococcaceaeUCG-010 and Christensenellaceae R-7 group. The results of the neutral model revealed that neutral processes predominantly governed the gut microbiota community assembly in different deer species, particularly in Père David's deer. PICRUSt2 predictions showed significant enrichment of fecal bacterial functions related to fatty acid, lipid, metabolic regulator, and amino acid biosynthesis. This comparative analysis sheds light on the microbial community structure, community assembly, and potential functions, offering improved insights into the management and conservation of deer species, especially Père David's deer. Future research might focus on exploring metagenomic functions and dynamics in wild settings or across different seasons using metagenomics or metatranscriptomics.